(3GdJYQja HQLGd (B[(3LGeY GdGegGJ(B] (3dGHf GdMGLHs - (3eMeO Hf YHO GdSdGe Hf ESMGb GHf CMeO GdBeOj GdeGdcj , YRGdOjf CHj YHO Gddgs; (3GHf GdMGLH , LeGd GdOjf CHh YeQh GHf GdMGLH, LeGd GdOjf CHh YeQh GHf GdMGLH,J (B646 (3g` s ((3YHOGdedc Hf eHGQc GdNdafj s)
(3ChdgG (B:s
(3hHYO , agPg ChQGb JJVef TjFkG eeG JjSQ GdEWdGY Ydjg ef GdCSeGAhGdCYdGe GdePchQjf ai GdoeNJUQ GdaQhYj ddTjN GdEeGe CHj YeQh Hf GdMGLH hhaGJge s
(3BNQgG (B:s
(3BNQ eGJgjC LeYg ef PcQ GdCSeGA GdePchQjf aj LGeY GdCegGJ hGdMeOddg aQZ efg eDdag SfI NeS hJSYjf hSHYeGFI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B39 - (3U(B135s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3LeYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
Keywords: (3GdJGQjNs